Pengukuran Kepuasan Nasabah Dengan Metode Quality Function Deployment (QFD) Dan Important Performance Analysis (IPA) Pada Jasa Bank - ardiansyah, faris ardiansyah; Sulistiyowati, Wiwik (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
This research aims to realize and maintain service quality because it can influence the level of customer satisfaction which will later influence customer loyalty to banking services at Bank XYZ. The methods used in this research are the Important Performance Quality (IPA) and Quality Function Deployment (QFD) methods. Important Performance Quality (IPA) is a method for representing the relative importance of an organization's performance in order to understand its basic attributes. Meanwhile, Quality Function Deployment (QFD) is a method for showing consumer needs and desires in products and services that have quality characteristics. Using the Important Performance Quality (IPA) and Quality Function Deployment (QFD) methods can determine the priority order for improvements based on service quality attributes and technical responses at Bank is one of the success factors for every service company.